KARAKTERISTIK SURFACE PARTIAL DISCHARGE DI SEKITAR ANTARMUKA PCB PADA PELAT-PELAT ELEKRODA PADA ISOLASI UDARA DAN MINYAK - Ardiansyah, Neris Peri; Pramudita, Resa (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
The use of high voltage equipment on the electronic power converter or power module has an influence on the equipment insulation system used. The resulting effect is a partial discharge (PD), where it is affected by the shape of the voltage, which is the phenomenon of PD is the beginning of the failure in equipment. In this study PD measurements were made with reference to the IEC 60270 Standard which uses the electrical method as a measurement used for PD testing on PCB materials with measuring instruments used are RC detectors and High-Frequency Current Transformers (HFCT). PD measurements are made by making a model of the electrodes used in testing to create a PD source. The electrode used is the Homogeneous electrode model of the plates. Tests on the PCB are performed to determine the surface discharge characteristics around the interface of the electrode plates. The parameters used in the measurement are Partial Discharge Inception Voltage (PDIV), Partial Discharge Extinction Voltage (PDEV), PD Waveforms, and PD Phase Patterns.